Students Intention to Join Merdeka Belajar Kampus Merdeka Based on Theory of Planned Behavior - Yohana F. Cahya Palupi Meilani; Pujianto Yugopuspito; Lala Palupi Santyaputri; Erric Raymond Tatimu; Ronald Suryaputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of the variable attitude toward behavior, subjective norms, perceived behavior control on students' intentions to join Merdeka Belajar Kampus Merdeka (MBKM) program based on the theory of planned behavior (TPB) in private university, Universitas Pelita Harapan (UPH). The MBKM program is expected to be able to bring private universities closer to the conditions of the Industrial World Business World to produce graduates who have the competencies according to the MBKM program offered. This study was conducted quantitatively on 379 UPH student respondents that has not joined MBKM program based on convenience sampling. Data processing was carried out with partial least squares using the Smart PLS program. The results show that attitude, subjective norms, and moral have a positive effect on students' intention to join MBKM program. The contribution of this research provides input for university administrators to know how to motivate students to have intention join MBKM program.